X‐Band DNP Hyperpolarization of Viscous Liquids and Polymer Melts. Issue 10 (10th March 2015) - Neudert, Oliver; Reh, Miriam; Spiess, Hans W.; Münnemann, Kerstin
<x xml:space="preserve">Abstract</x> NMR studies of synthetic polymers and biomacromolecules, which provide insight into the conformation and dynamics of these materials, can benefit strongly from the increased sensitivity offered by dynamic nuclear polarization (DNP) and other hyperpolarizing methods. In this study 1H DNP nuclear spin hyperpolarization of two polybutadiene samples, representing a supercooled liquid and an entangled polymer melt, is demonstrated at 0.35 T magnetic field strength and at temperatures between −80 and +50 °C. Electron spin polarization transfer from the α, γ‐bisdiphenylene‐β‐phenylallyl radical to the sample nuclei is achieved by the Overhauser and solid effect. DNP signal enhancements are studied, varying the electron spin resonance offset, microwave power, and sample temperature. The influence of spin relaxation times, line widths, and molecular dynamics are discussed. The results show promising, up to 15‐fold NMR signal enhancements using noncryogenic temperatures and an inexpensive setup that is less technically demanding than current high‐field DNP setups.